Activation of Both MAP Kinase and Phosphatidylinositide 3-Kinase by Ras Is Required for Hepatocyte Growth Factor/Scatter Factor–induced Adherens Junction Disassembly - Potempa, Sandra (The American Society for Cell Biology, 1998)
Hepatocyte growth factor/scatter factor (HGF/SF) stimulates the motility of epithelial cells, initially inducing centrifugal spreading of colonies followed by disruption of cell–cell junctions and subsequent cell scattering. In Madin–Darby canine kidney cells, HGF/SF-induced motility involves actin reorganization mediated by Ras, but whether Ras and downstream signals regulate the breakdown of intercellular adhesions has not been established. Both HGF/SF and V12Ras induced the loss of the adherens junction proteins E-cadherin and β-catenin from intercellular junctions during cell spreading, and the HGF/SF response was blocked by dominant-negative N17Ras. Desmosomes and tight junctions were regulated separately from adherens junctions, because they were not disrupted by V12Ras. MAP kinase, phosphatidylinositide 3-kinase (PI 3-kinase), and Rac were required downstream of Ras, because loss of adherens junctions was blocked by the inhibitors PD098059 and LY294002 or by dominant-inhibitory mutants of MAP kinase kinase 1 or Rac1. All of these inhibitors also prevented HGF/SF-induced cell scattering. Interestingly, activated Raf or the activated p110α subunit of PI 3-kinase alone did not induce disruption of adherens junctions. These results indicate that activation of both MAP kinase and PI 3-kinase by Ras is required for adherens junction disassembly and that this is essential for the motile response to HGF/SF.